HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) DENGAN LENGKUNG KAKI PADA ANAK USIA 10-12 TAHUN DI SD MUHAMMADIYAH 04 DEPOK - Zafira Jauza (2022)
Body mass index (BMI) is a reference used to determine the category of body weight composition. BMI measurement is also related to nutritional status that affects a person's health. In children who have excessive body weight, the arch of the foot will be flatfoot because the load is greater. So it can cause pain, injury, walking disorders, and imbalance to stand for a long time. Therefore, the purpose of this study was to determine the relationship between BMI and foot arch in children aged 10-12 years at SD Muhammadiyah 04 Depok. The design of this study using a cross-sectional conducted by observation method at a time without any follow-up or continuous. The sample in this study were children aged 10-12 years in SD Muhammadiyah 04 Depok which amounted to 52 people. The measurements taken were BMI by measuring weight and height, and foot arch by tracing the foot on paper using color paint. The results obtained after the research using the chi-square correlation test is p value = 0.025 so it can be concluded that there is a significant relationship between BMI and foot arch in children aged 10-12 years.